2021
DOI: 10.1038/s41541-021-00406-4
|View full text |Cite
|
Sign up to set email alerts
|

A single dose, BCG-adjuvanted COVID-19 vaccine provides sterilising immunity against SARS-CoV-2 infection

Abstract: Global control of COVID-19 requires broadly accessible vaccines that are effective against SARS-CoV-2 variants. In this report, we exploit the immunostimulatory properties of bacille Calmette-Guérin (BCG), the existing tuberculosis vaccine, to deliver a vaccination regimen with potent SARS-CoV-2-specific protective immunity. Combination of BCG with a stabilised, trimeric form of SARS-CoV-2 spike antigen promoted rapid development of virus-specific IgG antibodies in the blood of vaccinated mice, that was furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 42 publications
1
68
0
Order By: Relevance
“…Such non-specific protection by BCG against non-mycobacterial infections and perhaps other non-infectious disorders include induction of: (i) a heterologous TH1, TH17, and CD8+ lymphocytic response and (ii) a non-specific memory in innate immune cells (natural killer cells, monocytes, and macrophages) through epigenetic effects and metabolic rewiring in a paradigm known as "trained immunity" [33]. Of contemporary note is the investigation of BCG in the COVID-19 pandemic; BCG benefit has been shown in both animal COVID-19 studies and humans where BCG demonstrated a "synergy" with COVID-19 vaccination [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Such non-specific protection by BCG against non-mycobacterial infections and perhaps other non-infectious disorders include induction of: (i) a heterologous TH1, TH17, and CD8+ lymphocytic response and (ii) a non-specific memory in innate immune cells (natural killer cells, monocytes, and macrophages) through epigenetic effects and metabolic rewiring in a paradigm known as "trained immunity" [33]. Of contemporary note is the investigation of BCG in the COVID-19 pandemic; BCG benefit has been shown in both animal COVID-19 studies and humans where BCG demonstrated a "synergy" with COVID-19 vaccination [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…This concept, which remains controversial, is currently being formally tested in a number of clinical trials ( Junqueira-Kipnis et al, 2020 ; Pépin et al, 2021 ; Tsilika et al, 2021 Preprint ). In addition, recent preclinical work has demonstrated the use of BCG as an adjuvant to boost SCV2-specific vaccine-induced protection ( Counoupas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While BCG vaccination is routinely used in most countries as a TB prevention, the vaccine is generally given intradermally, and recent human studies showing protection by BCG against COVID-19 disease also used intradermal BCG (13). Like other animal studies using BCG in animal models of SCV2 (28) we used the intravenous route based on literature that IV BCG is far more potent against tuberculosis in non-human primates, and evidence that IV BCG reprograms bone marrow hematopoietic stem cells towards a more protective state against bacterial challenge (22). Nevertheless, SCV2 animal studies using percutaneous BCG have shown significant immunologic benefits at the level of flow cytometry (29), and we anticipate that many of the scRNAseq shifts which we observed in IV BCG vaccinated hamsters would be present following intradermal BCG albeit potentially at a lower level.…”
Section: Discussionmentioning
confidence: 99%